Diseño y elaboración de una galería virtual sobre los orígenes de las festividades religiosas en honor a la imagen de la santísima cruz del barrio la laguna, parroquia Ignacio Flores - Sánchez Logroño, Hernán Marcelo (2016)
Ecuador festivities, throughout its history are full of culture and tradition, they are manifestations of their way of living, thinking and acting. Through time Ecuador has established itself as a country rich in culture, religion and especially the traditions, characteristics of each people or group of people. Through this approach, the proposed work about the Festivities of la Santísima Cruz in La Laguna neighborhood, Latacunga canton, Cotopaxi province, made during the days of carnival, aims appreciation and dissemination of cultural and religion origin, being the image of la Santísima Cruz, the center and purpose of these celebrations, by the faithful who carry out the process of organizing these traditional festivals of culture and popular religiosity. The virtual gallery and proposal aims to publicize the origin of these celebrations for people in the sector and tourists who come each year to be part of this traditional religious festival.